Crystal form of ilastrant dihydrochloride as well as preparation method and application of crystal form of ilastrant dihydrochloride

CN119343330APending Publication Date: 2025-01-21CRYSTAL PHARMA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380032257.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-26
Filing Date
2023-05-24
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing crystal form of elastran dihydrochloride has problems such as low solubility, unsatisfactory fluidity and compressibility, and high adhesion, which affects the clinical efficacy of the drug and the processing during the production process.

Method used

A new crystal form CSII was developed, prepared by stirring and drying in chloroform, with higher solubility, better fluidity, better compressibility, lower adhesion and more uniform particle size distributed.

Benefits of technology

It improves the absorption and efficacy of the drug in the human body, reduces the risk of uneven preparation content, improves the tableting process during the production process, and ensures the stability and quality of the drug.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343330A_ABST
    Figure CN119343330A_ABST
Patent Text Reader

Abstract

The invention relates to a novel crystal form of ilastrant (hereinafter referred to as' Compound I ') dihydrochloride and a preparation method thereof, a pharmaceutical composition containing the crystal form, and application of the crystal form in preparation of estrogen receptor degradation agent drugs and drugs for treating estrogen receptor positive breast cancer or human epidermal growth factor receptor 2 negative breast cancer or ESR1 mutation breast cancer. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Crystal form of elastostat dihydrochloride, preparation method and use thereof Technical Field

[0001] The present invention relates to the field of crystal chemistry, and in particular to a crystal form of elastomeric dihydrochloride, a preparation method thereof, and uses thereof. Background Art

[0002] Breast cancer is a type of cancer that develops from breast tissue. When breast cancer cells test positive for estrogen receptors, it is called estrogen receptor-positive (ER+) breast cancer. HER2 (human epidermal growth factor receptor 2) is a receptor located on the surface of breast cells. When cancer cells do not contain high levels of HER2, they are HER2-negative (HER2-) breast cancer. Currently, breast cancer is the most common cancer worldwide, with the highest incidence rate among female malignancies, and over two million new diagnoses worldwide each year.

[0003] Elacestrant, a next-generation oral estrogen receptor degrader (SERD) developed in collaboration between Radius Health and Menarini Group, has been approved in the US for the treatment of advanced or metastatic breast cancer in postmenopausal women or men with ER+, HER2-, or ESR1 mutations who have progressed after at least one line of endocrine therapy. Elacestrant exhibits excellent selectivity for estrogen receptors and exhibits anti-estrogenic effects in various tissues.

[0004] The chemical name of elastatin is (R)-6-{2-{ethyl[4-(2-ethylaminoethyl)benzyl]amino}-4-methoxyphenyl}-5,6,7,8-tetrahydronaphthalen-2-ol (hereinafter referred to as "Compound I"). The structural formula of Compound I dihydrochloride is as follows:

[0005] It is well known in the art that drug polymorphism is a common phenomenon in small molecule drug development and a significant factor affecting drug quality. A crystal is a solid formed by the three-dimensional, ordered arrangement of compound molecules within a microstructure, forming a crystalline lattice. Polymorphism refers to the phenomenon of a single compound existing in multiple crystalline forms. A compound may exist in one or more crystalline forms, but their presence and properties cannot be specifically predicted. APIs with different crystalline forms have varying physicochemical properties, including chemical stability, thermal stability, solubility, hygroscopicity, and / or particle size. This can lead to varying dissolution and absorption of the drug in the body, thereby impacting the drug's clinical efficacy to a certain extent. Furthermore, APIs with different crystalline forms have varying manufacturability, including yield, purification properties, filtration properties, drying properties, and milling properties. Their stability to pressure during tableting can also affect processing during the API production process. Therefore, polymorphism is a crucial aspect of pharmaceutical research and quality control.

[0006] Currently, prior art WO2018129419 discloses Form 1, Form 2, and Form 3 of the dihydrochloride salt of Compound I. Prior art WO2020010216 discloses Form 1B of the dihydrochloride salt of Compound I. WO2023064519 discloses Form 6, Form 7, and Form 9 of the dihydrochloride salt of Compound I. The crystalline form CSII of the present invention is different from any of the aforementioned crystalline forms. Figure 1 of WO2020010216 shows that Form 1 transforms into Form 3 under high humidity conditions, Form 2 transforms into Form 3 when the humidity is below 40% RH, and Form 3 transforms into Form 2 when the humidity is above 40% RH. Table 17 of WO2020010216 discloses that Form 1B can remain stable at humidity above 90% RH, indicating that Form 1B is the most stable crystalline form in the prior art.

[0007] In addition, prior art WO2020167855, Scheme 1, Step 6, discloses a method for preparing a crystal of Compound I dihydrochloride, but does not disclose the XRPD data of the crystal. The inventors of the present application repeated the preparation method and confirmed that the resulting crystals were Form 1B in prior art WO2020010216.

[0008] Through the analysis of the above prior art, it can be seen that Form 1B is the crystal form with the best properties. However, Table 17 of the prior art WO2020010216 discloses that Form 1B is a very small flaky particle, and is mainly an agglomerate. The crystal form that is easy to agglomerate has an uneven particle size distribution, which increases the risk of uneven content of the drug preparation. Further, after in-depth research by the inventors of the present application, it was found that Form 1B also has the problems of low solubility, unsatisfactory fluidity and compressibility, and high adhesion. Low solubility is not conducive to the release and absorption of the drug in the human body. Poor fluidity and compressibility, and high adhesion may cause the raw material to be difficult to disperse evenly during the mixing process of the excipients, and the product tableting process is prone to unmolded, cracked, and disintegrated tablets.

[0009] To overcome the shortcomings of the prior art, a new crystalline form is still needed for the development of pharmaceuticals containing Compound I dihydrochloride. The inventors of the present application unexpectedly discovered that the crystalline form of Compound I dihydrochloride provided by the present invention has advantages in at least one of solubility, hygroscopicity, purification effect, stability, adhesion, compressibility, flowability, in vitro and in vivo dissolution, and bioavailability. In particular, while maintaining good stability, it has better solubility, purification effect, flowability, compressibility, adhesion, and uniform particle size distribution, which is of great significance for the development of pharmaceuticals containing Compound I.

[0010] Summary of the Invention

[0011] The present invention provides a new crystal form of Compound I dihydrochloride, a preparation method thereof, and a pharmaceutical composition containing the new crystal form.

[0012] According to the purpose of the present invention, the present invention provides a crystalline form of Compound I dihydrochloride, which is, without limitation, crystalline form CSII (hereinafter referred to as "crystalline form CSII").

[0013] On the one hand, using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form CSII has characteristic peaks at diffraction angles 2θ of 10.3°±0.2°, 12.1°±0.2°, and 15.4°±0.2°.

[0014] Furthermore, using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form CSII has characteristic peaks at one, or two, or three, or four of the diffraction angles 2θ of 7.9°±0.2°, 9.2°±0.2°, 13.8°±0.2°, and 11.0°±0.2°; preferably, the X-ray powder diffraction pattern of the crystalline form CSII has characteristic peaks at diffraction angles 2θ of 7.9°±0.2°, 9.2°±0.2°, 13.8°±0.2°, and 11.0°±0.2°.

[0015] On the other hand, using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form CSII has characteristic peaks at any 3, or 4, or 5, or 6, or 7, or 8, or 9, or 10 of the diffraction angle 2θ values ​​of 10.3°±0.2°, 12.1°±0.2°, 15.4°±0.2°, 7.9°±0.2°, 9.2°±0.2°, 13.8°±0.2°, 11.0°±0.2°, 11.5°±0.2°, 17.4°±0.2°, and 21.8°±0.2°.

[0016] Without limitation, using Cu-Kα radiation, the X-ray powder diffraction pattern of Form CSII is substantially as shown in FIG1 or FIG2 .

[0017] Without limitation, Form CSII is an anhydrate.

[0018] According to the purpose of the present invention, the present invention also provides a method for preparing the crystalline form CSII, which comprises:

[0019] The solid of compound I dihydrochloride was placed in chloroform, stirred, separated, and dried to obtain crystal form CSII.

[0020] The stirring temperature is preferably 25° C., more preferably 50° C.; and the stirring time is preferably more than 24 hours.

[0021] According to the purpose of the present invention, the present invention provides the use of the crystal form CSII for preparing other crystal forms or co-crystals of compound I and its salts.

[0022] According to the purpose of the present invention, the present invention provides a pharmaceutical composition comprising an effective therapeutic amount of crystalline form CSII and pharmaceutically acceptable excipients.

[0023] According to the purpose of the present invention, the present invention provides use of the crystal form CSII in preparing estrogen receptor degrader drugs.

[0024] According to the purpose of the present invention, the present invention provides the use of crystal form CSII in preparing drugs for treating estrogen receptor-positive breast cancer, human epidermal growth factor receptor 2-negative breast cancer or ESR1 mutation breast cancer.

[0025] Beneficial effects and technical problems solved by the present invention

[0026] The technical problem solved by the present invention is to provide a new crystal form different from the prior art crystal form. This crystal form has excellent stability and, compared with the prior art form 1B, has higher solubility, better fluidity, better compressibility, lower adhesion, better purification effect, no agglomeration, and more uniform particle size distribution, thereby solving the problems existing in the prior art.

[0027] The crystal form CSII provided by the present invention has the following unexpected beneficial effects:

[0028] (1) Compared with the prior art form 1B, the crystalline form CSII provided by the present invention has better solubility. In particular, the solubility in FeSSIF is more than twice that of the prior art form 1B.

[0029] Elastran is a poorly water-soluble drug belonging to BCS Class IV, which means it has low solubility and low permeability. Such drugs are not easily released and absorbed in the human body. The crystal form CSII provided by the present invention has higher solubility, which helps improve drug absorption in the human body.

[0030] (2) Compared with the prior art form 1B, the crystal form CSII provided by the present invention has a better purification effect. After the raw materials are prepared into the crystal form of the present invention, the purity is significantly improved. In a specific embodiment, after the crystal form CSII of the present invention is prepared using a raw material with a purity of 99.14%, the purity is increased to 99.80%, and the purity is increased by 0.60%. In particular, for impurities at RRTs of 0.84, 1.14, and 1.43, the crystal form CSII has a more obvious purification effect. The high chemical purity of the drug is of great significance for ensuring the efficacy and safety of the drug and preventing the occurrence of adverse drug reactions. The crystal form CSII provided by the present invention has a good purification effect and a strong impurity removal ability. A high-purity raw material drug can be obtained by crystallization, which effectively overcomes the shortcomings of low drug stability, poor efficacy, and high toxicity caused by low drug purity.

[0031] (3) Compared to the prior art Form 1B, the crystalline Form CSII provided by the present invention exhibits no agglomeration and a more uniform particle size distribution. This uniform particle size helps reduce solvent accumulation, improve product purity, reduce product residuals, ensure uniformity in drug formulation content, and reduce variability in in vitro dissolution.

[0032] (4) Compared with the prior art form 1B, the crystalline form CSII provided by the present invention has better flowability. The flowability evaluation results show that the flowability of the crystalline form CSII is significantly better than that of the prior art form 1B. The better flowability can avoid clogging of production equipment, improve production efficiency, ensure the content uniformity of the preparation, reduce weight variation, and improve product quality.

[0033] (5) Compared with the prior art form 1B, the crystalline form CSII provided by the present invention has superior compressibility. The good compressibility of the crystalline form CSII can effectively improve problems such as substandard hardness / friability and cracking in the tableting process, making the formulation process more reliable, improving product appearance, and enhancing product quality and production efficiency.

[0034] (6) Compared with the prior art form 1B, the crystalline form CSII provided by the present invention has lower adhesion. The adhesion evaluation results show that the adhesion amount of the crystalline form CSII is much lower than that of the prior art crystalline form. The lower adhesion performance effectively reduces the agglomeration of the raw material, can effectively improve or avoid the sticking and punching phenomena caused by dry granulation and tablet compression, is conducive to the dispersion of the raw material and the mixing with the excipients, improves the mixing uniformity during the mixing of the materials, and ultimately improves the product quality.

[0035] (7) The crystalline form CSII provided by the present invention has good physical stability under mechanical forces. The crystalline form CSII API maintains its crystal form after grinding and after the formulation process. Grinding or crushing the API is often required during the formulation process, and good physical stability can reduce the risk of API crystallinity reduction and crystal transformation during the formulation process. In addition, the crystalline form CSII API has good physical stability under different pressures, which is beneficial for maintaining the crystal form stable during the formulation tableting process.

[0036] (8) The crystalline CSII API and preparation provided by the present invention have good stability. The crystalline CSII API was placed under 25°C / 60% RH conditions for at least 6 months without any change in crystal form, and the purity remained basically unchanged during storage. After the crystalline CSII was mixed with excipients to make a pharmaceutical preparation, it was placed under 25°C / 60% RH conditions for at least 3 months without any change in crystal form, and the purity remained basically unchanged during storage. This shows that the crystalline CSII API and preparation have good stability under long-term conditions. The good physical and chemical stability of the API crystal form can ensure that the drug will not undergo crystal transformation during production and storage and that basically no impurities are generated. The crystalline CSII has good physical and chemical stability, which ensures that the quality of the API and preparation is consistent and controllable, and reduces changes in drug quality, bioavailability, and toxic side effects caused by changes in crystal form or impurities.

[0037] Furthermore, the crystalline CSII API maintained its crystal form unchanged after storage at 40°C / 75% RH for at least six months, and its purity remained essentially unchanged during storage. After crystalline CSII was mixed with excipients to form a pharmaceutical preparation, it was stored at 40°C / 75% RH for at least one month without changing its crystal form, and its purity remained essentially unchanged during storage. This indicates that the crystalline CSII API and preparation exhibited good stability under accelerated conditions. High temperatures and high humidity conditions caused by seasonal variations, regional climate differences, and environmental factors can affect the storage, transportation, and production of APIs and preparations. Therefore, the stability of APIs and preparations under accelerated conditions is crucial for pharmaceuticals. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is the XRPD pattern of crystal form CSII

[0039] Figure 2 is the XRPD pattern of crystal form CSII

[0040] Figure 3 is the TGA diagram of crystal form CSII

[0041] Figure 4 is a comparison of XRPD patterns of Form CSII before and after storage under different conditions (from top to bottom: before storage, after 6 months of storage at 25°C / 60% RH sealed with desiccant and antioxidant, and after 6 months of storage at 40°C / 75% RH sealed with desiccant and antioxidant).

[0042] Figure 5 is a comparison of XRPD images of Form CSII before and after ball milling (from top to bottom: after milling, before milling)

[0043] Figure 6 is an XRPD overlay of Form CSII before and after formulation (from top to bottom: blank powder mix, Form CSII after formulation, Form CSII)

[0044] Figure 7 is a comparison of XRPD patterns of the crystalline CSII preparation before and after storage under different conditions (from top to bottom: before storage, after storage at 25°C / 60% RH with 1g of desiccant and 1g of antioxidant for 3 months, and after storage at 40°C / 75% RH with 1g of desiccant and 1g of antioxidant for 1 month). DETAILED DESCRIPTION

[0045] The present invention is described in detail with reference to the following examples, which describe in detail the preparation and use of the crystalline forms of the present invention. It will be apparent to those skilled in the art that many variations in both materials and methods may be made without departing from the scope of the present invention.

[0046] The abbreviations used in the present invention are explained as follows:

[0047] RH: relative humidity

[0048] XRPD: X-ray powder diffraction

[0049] TGA: Thermogravimetric analysis

[0050] HPLC: High Performance Liquid Chromatography

[0051] HDPE: High-density polyethylene

[0052] FeSSIF: artificial intestinal fluid in the fed state

[0053] Instruments and methods used to collect data:

[0054] The X-ray powder diffraction pattern of the present invention was collected on a Bruker X-ray powder diffractometer. The method parameters of the X-ray powder diffraction of the present invention are as follows:

[0055] X-ray source: Cu, Kα

[0056] 1.54060; 1.54439

[0057] Kα2 / Kα1 intensity ratio: 0.50

[0058] The thermogravimetric analysis (TGA) graphs of the present invention were collected on a TA Q500. The method parameters of the thermogravimetric analysis (TGA) of the present invention are as follows:

[0059] Scan rate: 10℃ / min

[0060] Shielding gas: N2

[0061] The particle size distribution results described herein were collected using a Malvern Mastersizer 3000 laser particle size analyzer. This test employed a wet method using a Hydro MV dispersant and Isopar G as the dispersion medium. The laser particle size analyzer parameters were as follows:

[0062] The test methods for the contents of the related substances and compound I described in the present invention are shown in Table 1.

[0063] Table 1

[0064] The test method for dynamic solubility of the present invention is shown in Table 2.

[0065] Table 2

[0066] The chloride ion content testing method of the present invention is shown in Table 3.

[0067] Table 3

[0068] The "stirring" is accomplished by conventional methods in the art, such as magnetic stirring or mechanical stirring, with a stirring speed of 50-1800 rpm, wherein the magnetic stirring speed is preferably 300-900 rpm, and the mechanical stirring speed is preferably 100-300 rpm.

[0069] The separation is accomplished by conventional methods in the art, such as centrifugation or filtration. The centrifugation operation is as follows: the sample to be separated is placed in a centrifuge tube and centrifuged at a rate of 10,000 rpm until all solids settle to the bottom of the centrifuge tube.

[0070] The drying process is accomplished using conventional methods in the art, such as vacuum drying, forced air drying, or air drying. The drying temperature can be room temperature or higher, preferably room temperature to about 60°C, or to 50°C, or to 40°C. The drying time can be 2-48 hours, or overnight. Drying is performed in a fume hood, forced air oven, or vacuum oven.

[0071] The “characteristic peak” refers to a representative diffraction peak used to identify crystals. When Cu-Kα radiation is used for testing, the 2θ value of the diffraction peak can usually have an error of ±0.2°.

[0072] In the present invention, "crystals" or "crystal forms" can be characterized by X-ray powder diffraction. Those skilled in the art will appreciate that X-ray powder diffraction patterns can vary depending on instrument conditions, sample preparation, and sample purity. The relative intensities of diffraction peaks in an X-ray powder diffraction pattern may also vary with experimental conditions, so the diffraction peak intensities cannot be the sole or decisive factor in determining a crystal form. In fact, the relative intensities of diffraction peaks in an X-ray powder diffraction pattern are related to the preferred orientation of the crystal. The diffraction peak intensities shown herein are illustrative and not intended for absolute comparison. Therefore, those skilled in the art will appreciate that the X-ray powder diffraction patterns of the crystal forms claimed by the present invention do not necessarily have to be identical to those in the Examples described herein. Any crystal form having X-ray powder diffraction patterns that are identical or similar to the characteristic peaks in these patterns falls within the scope of the present invention. Those skilled in the art can compare the X-ray powder diffraction patterns listed herein with those of an unknown crystal form to determine whether the two patterns reflect the same or different crystal forms.

[0073] In some embodiments, the crystalline form CSII of the present invention is pure and substantially free of any other crystalline forms. As used herein, "substantially free" when referring to a new crystalline form means that the crystalline form contains less than 20% (by weight) of other crystalline forms, particularly less than 10% (by weight) of other crystalline forms, more particularly less than 5% (by weight) of other crystalline forms, and even more particularly less than 1% (by weight) of other crystalline forms.

[0074] The term "about" in the present invention, when used to refer to a measurable value, such as mass, time, temperature, etc., means that there is a certain floating range around the specific value, which can be ±10%, ±5%, ±1%, ±0.5%, or ±0.1%.

[0075] Unless otherwise specified, the following examples were performed at room temperature and ambient humidity. "Room temperature" is not a specific temperature value, but rather refers to a temperature range of 10-30°C. "Ambient humidity" is not a specific humidity value, but may range from 10% RH to 90% RH, 20% RH to 80% RH, or 30% RH to 70% RH.

[0076] According to the present invention, the compound I and / or its salt as a raw material includes but is not limited to solid form (crystalline or amorphous), oily, liquid form and solution. Preferably, the compound I as a raw material is in solid form.

[0077] Compound I and / or its salt used in the following examples can be prepared according to the prior art, for example, according to the method described in WO2018129419.

[0078] Example 1 Preparation Method of Crystalline Form CSII

[0079] 10.6 mg of Compound I dihydrochloride solid was weighed into a glass vial, followed by the addition of 0.1 mL of chloroform. The mixture was suspended and stirred at 50°C for 21 days, then transferred to -20°C and allowed to stand for 6 days. The solid was separated and dried under vacuum at room temperature overnight to obtain a dry solid.

[0080] After testing, the obtained dry solid was found to be the crystalline form CSII of the present invention. Its X-ray powder diffraction pattern is shown in FIG1 , and the X-ray powder diffraction data are shown in Table 4.

[0081] Table 4

[0082] Example 2 Preparation Method of Crystal Form CSII

[0083] 99.7 mg of Compound I dihydrochloride solid was weighed into a glass vial, followed by the addition of 1 mL of chloroform and an appropriate amount of seed crystals of Form CSII. The mixture was suspended and stirred at 50° C. for 3 days, and then transferred to room temperature and vacuum dried for 2 days to obtain a dry solid.

[0084] After testing, the obtained dry solid was found to be the crystalline form CSII of the present invention. Its X-ray powder diffraction pattern is shown in FIG2 , and the X-ray powder diffraction data are shown in Table 5.

[0085] Table 5

[0086] Example 3 TGA of Form CSII

[0087] The TGA of Form CSII is shown in Figure 3 , which shows almost no weight loss before 100°C.

[0088] Example 4 Chloride ion content of crystal form CSII

[0089] The contents of chloride ions and free base in the crystalline form CSII of the present invention were tested, and the molar ratio was calculated. The results are shown in Table 6. The results show that the molar ratio of chloride ions and free base in the crystalline form CSII of the present invention is 2.0, and the crystalline form CSII of the present invention is a dihydrochloride salt form of Compound I.

[0090] Table 6

[0091] Example 5 Dynamic Solubility of Crystalline Form CSII

[0092] When conducting drug solubility testing to predict in vivo performance, it's crucial to closely mimic in vivo conditions. For oral drugs, FeSSIF (simulated fed-state intestinal fluid) can simulate in vivo conditions and predict the effects of feeding. Solubility measurements in this medium more closely resemble solubility in the human body.

[0093] Approximately 10 mg each of the crystalline Form CSII of the present invention and the prior art Form 1B were dispersed in 1 mL of FeSSIF to prepare a suspension. The suspension was equilibrated at 37°C for 30 minutes and then filtered to obtain a saturated solution. The sample content (mg / mL) in the saturated solution was measured by high-performance liquid chromatography. The results are shown in Table 7. The results show that the crystalline Form CSII has a higher solubility in FeSSIF, which is 2.2 times that of the prior art Form 1B.

[0094] Table 7

[0095] Example 6 Purification Effect of Crystal Form CSII

[0096] Crystalline Form CSII of the present invention and Form 1B of the prior art were prepared using the same starting materials. The chemical purity of the starting materials, Crystalline Form CSII of the present invention, and Form 1B of the prior art was determined by HPLC, and the test results are shown in Table 8. The results show that when Crystalline Form CSII and Form 1B are prepared using the same starting materials, Crystalline Form CSII has a higher purity, especially for impurities at RRT (relative retention time) of 0.84, 1.14, and 1.43, Crystalline Form CSII has a better purification effect, and the impurity content is below the detection limit.

[0097] Table 8 ND: Not Detected

[0098] Example 7 Morphology of Form CSII

[0099] An appropriate amount of the present invention's crystal form CSII was placed on a glass slide, dispersed with vacuum pump oil, covered with a coverslip, and photographed using a polarizing microscope at a magnification of 200. The results showed that the crystal form CSII had no agglomeration.

[0100] Example 8 Particle size distribution of crystal form CSII

[0101] Appropriate amounts of the present invention's crystalline form CSII and the prior art form 1B were taken and subjected to particle size distribution testing to obtain the average particle size calculated by volume, the particle size corresponding to 10% of the particle size distribution (volume distribution) (D10), the particle size corresponding to 50% of the particle size distribution (volume distribution) (D50), and the particle size corresponding to 90% of the particle size distribution (volume distribution) (D90). The test results are shown in Table 9. The results show that compared with the prior art form 1B, the particle size distribution of the present invention's crystalline form CSII is more uniform.

[0102] Table 9

[0103] Example 9 Flowability of Form CSII

[0104] During the formulation process, the compressibility index is usually used to evaluate the flowability of powders or granules. The determination method is to gently fill a certain amount of powder into a graduated cylinder and measure the volume before tapping. Then, use the tapping method to make the powder in the most compact state and measure the volume after tapping. Then, calculate the bulk density ρ0 and the tapped density ρf. The compressibility index is calculated according to the formula c = (ρf - ρ0) / ρf. According to USP General Charters: <1174> The fluidity determination criteria in Powder Flow and the fluidity results are shown in Table 10. The results show that the fluidity of the crystal form CSII is significantly better than that of the prior art form 1B.

[0105] Table 10

[0106] Example 10 Compressibility of Form CSII

[0107] The tablets were compressed using an ENERPAC manual tablet press. A Φ6mm circular flat punch was selected, and 60mg of the crystal form CSII of the present invention and the prior art form 1B were added respectively. The tablets were pressed into round tablets using a pressure of 5kN. The tablets were placed at room temperature for 24 hours. After complete elastic recovery, the radial crushing force (hardness, H) was tested using a tablet hardness tester. A vernier caliper was used to measure the diameter (D) and thickness (L) of the tablets, and the tensile strength of the powder was calculated using the formula T=2H / πDL. Under a certain pressure, the greater the tensile strength, the better its compressibility. The results are shown in Table 11. The results show that compared with the prior art form 1B, the crystal form CSII of the present invention has greater tensile strength and better compressibility.

[0108] Table 11

[0109] Example 11 Adhesion of Crystalline Form CSII

[0110] An ENERPAC manual tablet press was used for tableting. Approximately 30 mg of the present invention's crystal form CSII and the prior art form 1B were added to a Φ8 mm circular intrinsic dissolution rate (IDR) mold, and tableting was performed using a pressure of 10 kN. After tableting, the tablets were left for about half a minute, and the amount of powder adsorbed by the punch was weighed. After two consecutive compressions using this method, the average amount of punch adhesion during the compression process was calculated. Specific experimental results are shown in Table 12. The results show that the present invention's crystal form CSII has lower adhesion than the prior art form 1B.

[0111] Table 12

[0112] Example 12 Stability of Crystal Form CSII

[0113] Appropriate amounts of Form CSII of the present invention were stored at 25°C / 60% RH and 40°C / 75% RH, respectively, and the purity and crystal form were determined using HPLC and XRPD. The results are shown in Table 13, and a comparative XRPD diagram is shown in Figure 4. These results demonstrate that Form CSII is stable for at least six months at both 25°C / 60% RH and 40°C / 75% RH, demonstrating its excellent stability under both long-term and accelerated conditions.

[0114] Table 13

[0115] Example 13 Stability of Form CSII under Mechanical Force

[0116] About 20 mg of the crystalline form CSII of the present invention was taken and pressed into tablets using a Φ6 mm round flat punch at different pressures. XRPD tests were performed before and after tableting. The test results are shown in Table 14. The results show that the crystalline form CSII has good stability under different pressures.

[0117] Table 14

[0118] About 20 mg of the present invention's crystal form CSII was placed in a centrifuge tube, zirconium beads were added, and ball milling was performed at 500 rpm for 10 minutes. XRPD analysis was performed before and after milling, and the test results are shown in Figure 5. The results show that the crystal form CSII did not transform into a crystal after ball milling, and the milling stability was good.

[0119] Example 14 Preparation of Form CSII

[0120] Form CSII was prepared using the formulation described in Table 15 and the process described in Table 16. XRPD patterns of blank powder mixes and samples before and after the formulation were analyzed, as shown in Figure 6. These results demonstrate that Form CSII remained stable before and after the formulation.

[0121] Table 15

[0122] Table 16

[0123] Example 15 Stability of Crystalline Form CSII Preparation

[0124] The crystalline Form CSII preparation was sealed, packaged with 1g of desiccant and an antioxidant, and then stored at 25°C / 60% RH and 40°C / 75% RH. Samples were taken to test the crystal form and purity, and the stability of the crystalline Form CSII preparation was investigated. The results are shown in Table 17, and the XRPD comparison diagram is shown in Figure 7. The results show that the crystalline Form CSII preparation can remain stable for at least 3 months at 25°C / 60% RH and for at least 1 month at 40°C / 75% RH. Therefore, the crystalline Form CSII preparation maintains good stability under both long-term and accelerated conditions.

[0125] Table 17

[0126] The above embodiments are intended only to illustrate the technical concepts and features of the present invention. Their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent changes or modifications made in accordance with the spirit of the present invention are intended to be covered by the scope of protection of the present invention.

Claims

1. A crystalline form of compound I dihydrochloride, characterized in that: Using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic peaks at 2θ values ​​of 10.3°±0.2°, 12.1°±0.2°, and 15.4°±0.2°.

2. The crystalline form of Compound I dihydrochloride according to claim 1, characterized in that Using Cu-Kα radiation, its X-ray powder diffraction pattern has a characteristic peak at at least one of 2θ values ​​of 7.9°±0.2°, 9.2°±0.2°, 13.8°±0.2°, and 11.0°±0.2°.

3. The crystalline form of Compound I dihydrochloride according to claim 1, characterized in that: Using Cu-Kα radiation, its X-ray powder diffraction pattern is basically as shown in Figure 1 or Figure 2.

4. The crystalline form of Compound I dihydrochloride according to claim 1, characterized in that It is anhydrous.

5. A pharmaceutical composition comprising a therapeutically effective amount of the crystalline form of Compound I dihydrochloride according to claim 1 and a pharmaceutically acceptable excipient.